Genetic suppression of Gαs protein provides rate control in atrial fibrillation - Lugenbiel, Patrick; Thomas, Dierk; Kelemen, Kamilla; Trappe, Kerstin; Bikou, Olympia; Schweizer, Patrick Alexander; Voss, Frederik; Becker, Rüdiger; Katus, Hugo; Bauer, Alexander (Basic research in cardiology, 2012)
Gene therapy-based modulation of atrioventricular (AV) conduction by overexpression of a constitutively active inhibitory Gα i protein effectively reduced heart rates in atrial fibrillation (AF). However, catecholamine stimulation caused an excessive increase in ventricular rate. We hypothesized that modest genetic suppression of a stimulatory G protein in the AV node would allow persistent rate control in acute AF and would prevent undesired heart rate acceleration during β-adrenergic activation. Atrial fibrillation was induced in 12 pigs by atrial burst pacing via an implanted cardiac pacemaker. Study animals were then assigned to receive either Ad-siRNA-Gαs gene therapy to inactivate Gαs protein or Ad-β-gal as control. Gαs protein inactivation resulted in a 20 % heart rate reduction (P < 0.01). AH and HV intervals were prolonged by 37 ms (P < 0.001) and 28 ms (P < 0.001), respectively, demonstrating atrioventricular conduction delay. Impairment of left ventricular ejection fraction (LVEF) during AF was attenuated by Gαs suppression (LVEF 49 %) compared with controls (LVEF 34 %; P = 0.03). Isoproterenol application accelerated ventricular heart rate from 233 to 281 bpm (P < 0.001) in control animals but did not significantly affect pigs treated with Ad-siRNA-Gαs (192 vs. 216 bpm; P = 0.19). In conclusion, genetic inhibition of Gαs protein in the AV node reduced heart rate and prevented AF-associated reduction of cardiac function in a porcine model. Rate control by gene therapy may provide an alternative to current pharmacological treatment of AF.